O problema da fundamentação moral: uma investigação das teorias de Jürgen Habermas - Persch, Danilo (Universidade Federal de São Carlos, 2009)
The goal of this thesis is to study the Jürgen Habermas theories, focussing on the communicative action and the ethics of discourse. The thematic of the communicative action deals with a linguistic tour , in other words, Habermas starts to analyze the society not from a productive paradigm, known as a philosophical-historical inheritance which comes from Marx, but from an intersubjective communication paradigm. This new conception of society also requests a re-orientation under the perspective of how should be grounded the values and moral standard rules. In this sense, Habermas build together with Karl-Otto Apel the ethics of discourse, which transcribes the assumptions of the pragmatic language needed to a rational justification of standard rules from agreements or consensus. The procedure in the search for consensus is made through speeches (dialogues), which depend on a number of conditions, such as: equal rights of participation, absence of internal and external coercion, mutual recognition of all those affected by the effects of a rule, etc. With such a point of view, Habermas intends to seek to ensure the universality of the moral principle, as well as solve the problem of ethnocentrism, which caracterize the major part of the contemporary culture. In a globalized society in the technical levels, economic and social as the actual, but marked by a serious problems which affects the environment and stimulate the exploitation of labor and corruption, etc. the ethics of discourse presents itself as an attempt at moral reasoning very promising.
Keywords: Ética; Diálogo; Ética - discursos; Habermas, Jürgen, 1929-; Fundamentação moral; Agir comunicativo; Racionalidade; Consenso; Moral reasoning; Communicative action; Ethics of discourse; Rationality; Consensus; CIENCIAS HUMANAS::FILOSOFIA